Efek Ambang Batas Inflasi terhadap Pertumbuhan Ekonomi di Indonesia - Putri, Adelia; Anward, Ryan Juminta (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
This study analyzes whether the inflation threshold's effect impacts economic growth and determines the relationship between inflation and economic development. The data used in this study were obtained from the OECD: Economic Growth and Inflation, Investment, Money Supply, and Population Growth. This study uses time-series data from 1970-2019 using a threshold estimation model. The analysis technique used is multiple regression with the OLS method. The results of this study estimate an inflation threshold of 5%. Inflation with a point of 5% has a statistically negative and significant impact on economic growth. However, there is no evidence that an inflation rate below the 5% threshold can increase economic growth in Indonesia.